Subsurface Geological Evaluation of the Central Sumatra Basin in Relation to the Presence of Heavy Oil - Julikah Julikah; Ginanjar Rahmat; Muhammad Budisatya Wiranatanegara (Testing Center for Oil and Gas LEMIGAS, 2021)
Central Sumatra Basin has been proven as a mature basin that produces large amounts of conventional oil. In fact, some of the existing oil fi elds are heavy oil containing such as Duri, Sebanga, Rantau Bais, and Kulin fi elds with their API Gravity values of lower than 25o . Apart from those oil fi elds the Central Sumatra Basin is expected to bear signifi cant heavy oil potential. In this light, this paper emphasizes discussion of subsurface geological evaluation on suspected fi elds/areas that contain heavy oil. This evaluation serves as a preliminary step in investigation of heavy oil resources/reserves in the basin. Analysis results on stratigraphic sequence and seismic interpretation provide information support facts over presence of heavy oil that are usually associated to main faults of Dalu-Dalu, Rokan, Sebanga, Petapahan, Pulau Gadang, and Kotabatak. Large tectonic events as a compression phase in the Middle Miocene – recent developed regional uplift and formed main thrust faults system, anticline structures due to the creature of basement highs, during which the F3 was deposited. The thrust faults system are important in the process of heavy oil generation in which surface water encroached into uplifted oil traps hence triggering heavy oil transformation mechanisms of biodegradation and water washing. This study provides illustration over sequences the heavy oil is generated in and their dimension in relation to area of structural anticlines. Based on available data, evaluation on subsurface geology has shown that anticlinal structures containing heavy oil tend to be characterized by near surface uplift (Basement up to 500 - 750 ms), whereas structures with lesser certainty in heavy oil containment tend show lower degrees of uplift marked by basement depth around 1000 ms or deeper. In general, seismic interpretation has shown that heavy oil is contained some sequences within sequences of 4 to 7 (equivalent to Menggala, Bekasap, Bangko, and Duri-Telisa formations).